Pengembangan Bahan Ajar Menggunakan Kvisoft Flipbook Maker Pada Materi Program Linear Submateri Pertidaksamaan Linear Dua Variabel Pada Siswa Kelas XI SMA Negeri 1 Langowan - Monica Pricilia Kapele; Vivian E. Regar; Derel Filandy Kaunang (International Forum of Researchers and Lecturers, 2024)
This research aims to determine whether the development of teaching materials using the Kvisoft flipbook maker application on linear program material, the sub-material of linear inequalities in two variables, affects learning outcomes. This research method uses research and development, with 25 students as subjects. The research results show that in the effectiveness test, it was found that 21 out of 25 students were declared complete in learning mathematics using teaching modules using Kvisoft flipbook maker on linear program material developed by the author. Meanwhile, Class So's teaching module developed in this research was effective.